MENINGKATKAN HASIL BELAJAR PADA MATERI PECAHAN MUATAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS IV SDN HANDIL BAKTI. - Muhyidin, Muhammad; Sunarno, Sunarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The issue addressed in this research is the low academic performance of fourth-grade students at SDN Handil Bakti in mathematics, particularly in the topic of fractions. This challenge is linked to the application of unsuitable instructional models and methods that do not sufficiently promote active student engagement. Moreover, there is a lack of contextualized practice questions that could support students in grasping and applying the concept of rectangular prism volume. To overcome this problem, the Problem-Based Learning (PBL) model was introduced into the instructional process. This study aims to examine teacher performance and analyze both student engagement and learning achievement through the use of the Problem-Based Learning (PBL) approach. This research employed a Classroom Action Research (CAR) methodology, which was implemented across two cycles. The participants included 24 fourth-grade students at SDN Handil Bakti during the 2024/2025 academic year, consisting of 9 boys and 15 girls. The study gathered both qualitative and quantitative data. Observations of teacher and student activities provided qualitative insights, while quantitative data were collected through individual written assessments. The analysis was carried out using percentage-based calculations and predetermined standards for classical learning mastery. Findings revealed that teacher activity was rated